PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SD SWASTA ARVENA SEI PEJANGKI - Mimbar, Wahyul; Kurniaman, Otang; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study was conducted because of the low ability to read the beginning of first grade elementary school SD Swasta Arvena Sei Pejangki. Of the 47 students who received a lower category there are 35 students (74.46%), moderate category there are 11 students (23.40%) and high category 1 students (2.12%) with an average value of 49.47. The purpose of this study to improve students' reading ability of Grade I SD Swasta Arvena Sei Pejangki by implementing cooperative learning model picture and picture. Results of preliminary data research students who are low category there are 35 students (74.46%), students were categorized being there are 11 students (23.40%) and students who were high category No 1 students (2.12%) with an average value category 49.47 low. In the first cycle of students' reading ability has increased. Students who are low category, there are 29 students (61.70%), students were categorized being there are 13 students (27.65%) and students who were high category there are 5 students (10.63%) with an average value of 64.36 categorized low. In the second cycle back to increase students' reading ability. Students who are low category reduced to 17 students (36.17%), students were categorized being increased to 15 students (31.91%) and the high category also increased to 16 students (34.04%) with the average value 79.43 average category being. Activities of teachers at each meeting have increased activity of teachers in learning. At the first meeting of the cycle I obtained a score of 30 with a percentage of 75% categorized either. The percentage increased to 32 with 80% categorized either. While on the second cycle of teacher activity has risen back to the first meeting of the second cycle obtain a score of 35 with a percentage of 87.5% is very good category. And at the second meeting of the second cycle increased to 37 with a percentage of 92.5% is very good category. Activities meeting 1 cycle I obtained a score of 28 with a percentage of 70% good category. Increased to 30 with a percentage of 75% categorized either. While on the second cycle of student activity has risen back to the first meeting of the second cycle obtain a score of 32 with a percentage of 80% good category. And at the second meeting of the second cycle increased to 35 with a percentage of 87.5% is very good category. Keywords : Picture and picture , the ability to read the beginning